The Purposes of Marriage and its Hierarchy according to Al-Ghazālī on the Iḥyā’ Ulūm al-Dīn based on Mubādalah Perspective - Heru Susanto; Abdul Ghofur; Abu Rokhmad; Agustina Kumala Dewi Sholihah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
Al-Ghazālī is recognized as a distinguished scholar who adeptly integrates the principles of fiqh ‘Islamic jurisprudence’ with tasawwuf ‘Islamic mysticism’, achieving a balance between naqlī ‘transmitted knowledge’ and 'aqlī ‘rational knowledge’, as articulated in his seminal work, Iḥyā' 'Ulūm al-Dīn. However, his perspectives on women's issues, particularly regarding the purpose of marriage, have been characterized as non-moderate, prompting some scholars to label him a misogynist. This study aims to elucidate and analyze Al-Ghazālī's views on the purpose of marriage and its hierarchical structure through the lens of Mubādalah ‘reciprocity’. This research employs qualitative literature review methodologies supported by a philosophical framework. Primary data are sourced from Al-Ghazālī's works, namely Iḥyā' 'Ulūm al-Dīn and Kasr al-Shahwatain. Secondary data encompass a range of academic books, journal articles, and additional references that substantiate the research findings. The collected data are subjected to descriptive-analytical techniques for thorough review and analysis. The research outcomes indicate the following: First, Al-Ghazālī highlights the hierarchy of marriage purposes grounded in the levels of maqāṣid al-syarī’ah, which consist of ḍarūriyāt ‘necessities’, ḥājiyāt ‘needs’, and taḥsīniyāt ‘desirables’. Second, from the perspective of Mubādalah, Al-Ghazālī's views on the purpose of marriage, as presented in Iḥyā' 'Ulūm al-Dīn, do not align with the principles of Mubādalah and exhibit gender bias. This misalignment is evident in several aspects: (1) At the pre-marriage stage, Al-Ghazālī positions men as the decision-makers in the selection of a spouse, while women are relegated to the status of the chosen objects. (2) There exists an incongruity between the hierarchy of marriage goals from Al-Ghazālī's perspective and the principles of Mubādalah. (3) Al-Ghazālī delineates the husband-wife relationship within a superior-inferior framework. (4) He emphasizes the roles of women primarily within domestic spheres. Al-Ghazālī's views are undoubtedly shaped by the socio-historical context of his era, as well as his identity as a şūfi. This research aspires to contribute to the discourse surrounding the evolution of Islamic family law legislation, advocating for the recognition and safeguarding of women’s rights and roles in a more equitable manner.